Hubungan Perceived Social Support dan Academic Burnout pada Mahasiswa Tingkat Akhir - Sierra Sinta Sunarso Putri; Mimbar Oktaviana (Jurnal Ragam Pengabdian, 2026)
Final-year psychology students face high academic demands during the completion phase of their studies, making them vulnerable to academic burnout. One factor that is presumed to play a role in alleviating academic exhaustion is perceived social support, which is an individual's perception of social support received from their surrounding environment. This study aims to examine the relationship between perceived social support and academic burnout in final-year psychology students. The study uses a quantitative approach with a cross-sectional correlational design. The participants consisted of 174 final-year psychology students from Universitas Negeri Surabaya, selected using purposive sampling. The research instruments used in this study were the Maslach Burnout Inventory- Student Survey (MBI-SS) and the Multidimensional Scale of Perceived Social Support (MSPSS) Indonesian-adapted version. Data analysis was conducted using Spearman's correlation because the data were not normally distributed. The results of the study showed a weak and non-significant negative correlation between perceived social support and academic burnout (ρ = -0.144; p = 0.058). Additional analysis indicated differences in the level of academic burnout based on residence, where students living in boarding houses had higher burnout levels compared to students living with their families. These findings underscore the importance of considering contextual factors in understanding academic burnout among final- year psychology students.